Acoustic monitoring and response of katydids (Orthoptera: Tettigoniidae) to the landscape mosaic in a Biosphere Reserve - Thompson, Aileen Celeste (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.